A CRITICAL REVIEW ON GUDUCHI (TINOSPORA CORDIFOLIA (WILLD.) MIERS) AND ITS MEDICINAL PROPERTIES - Mani Tripathi, Bhoopendra; Singh, D.C.; Chaubey, Suresh; Kour, Gagandeep; Arya, Rishi (International Journal of Ayurveda and Pharma Research, 2015)
All edible things which are used in our food are full of free radicals. So there develops a need to free our body from these free radicals and the things which can help are the natural antioxidants. Guduchi (Amrita, Giloy) is the best of them which is abundantly available in all over India. Though almost all of its parts are used in traditional systems of medicines, leaves, stem and roots are the most important parts which are used medicinally. Guduchi (Tinospora cordifolia (Wild.) Miers ex Hook.F. & Thoms.) is a versatile resource for all forms of life. It belongs to family Menispermaceae. It contains many different chemicals that affect the body. Some of these chemicals have an antioxidant effect. While other might increases the ability of bodys immune system and some chemicals have activity against cancer cells also. The Rasayana accords longevity, enhance the memory, improve the health, bestows youth, better complexion, voice, energy and lustre the skin. So it is one of the most effective Rasayana and rejuvenative. It works well on all the seven Dhatus (tissues) and keeps the system in balance. This review gives a birds eye view on the therapeutic uses of various parts and extract of T. cordifolia to enrich our knowledge about this plant.